Microwave-Assisted Synthesis of Quinazolines and Quinazolinones: An Overview - Mohammadkhani, Leyla; Heravi, Majid M. (Frontiers in Chemistry, 2020)
Microwave irradiation (MWI) as a unique, effective, sustainable, more economic, and greener source of energy compared to conventional heating is applied in different organic transformations resulted in the rapid formation of the desired compounds due to thermal/kinetic effect. In this review, we try to underscore the applications of microwave irradiation (MWI) in the synthesis of quinazoline and quinazolinone derivatives, being achieved and reported in the last two decades.